Carbon nanotube thin film transistors by droplet electrophoresis. (March 2017) - Lefebvre, J.; Ding, J.
Graphical abstract: Abstract: Spontaneously charged aerosol droplets, each containing a few single-walled carbon nanotubes wrapped in conjugated polymers were precipitated on a target substrate using electrostatic forces. Nanotube networks were assembled on a variety of dielectric surfaces including polymers with low surface energy: Good transistor performance was achieved in all cases. Under proper regime of electrostatic and flow fields, patterns were produced in a maskless fashion and feature sizes below 150 μm were demonstrated.